Typhonium kbangense, a new species of Araceae (Aroidea–Areae) from Central Vietnam. Issue 8 (28th June 2022) - Du Nguyen, Van; Toan Le, Chi; Diep Dinh, Quang; Van Anh Nguyen, Thi; Tien Tran, Van; Croat, Thomas B.
Abstract : Typhonium kbangense is described as a new species from Vietnam. It is one of eleven species recently found in central and southern Vietnam. It belongs to the pedate leaf blade group of species and is closest to T. bachmaense and T. dongnaiense, but is differentiated from the two latter by having much longer sterile flowers, not dense as in T. dongnaiense, and without being clavate apically as in T. bachmaense . A table of morphological characters for the three species, the ecological characteristics, specific habitat and conservation status of the new species are estimated and provided.